Analisis Kualitas Isi Buku Teks Matematika SMP Kelas VIII Berdasarkan Taksonomi Bloom - Abdi, Khairil; Mardhiah; Latuconsina, Nurkhalisah (Alauddin Journal of Mathematics Education, 2022)
This study aims to find out how the quality of the content of the Mathematics Textbook for Junior High School Class VIII Semester 2 Curriculum 2013 based on bloom taxonomy. This research is a type of descriptive research that uses a qualitative approach. The research instrument used is a human instrument. The data source consists of primary data sources, namely the Mathematics Textbook of Junior High School Class VIII Semester 2 Curriculum 2013 published by the Ministry of Education and Culture and secondary data sources, namely relevant books, journals, and the results of previous research. Based on the results of research and discussion, it can be concluded that the mathematics textbooks of SMP Class VIII Semester 2 Curriculum 2013 based on bloom taxonomy, obtained research results in each chapter as follows; in chapter 6 the percentage is 47%, in chapter 7 the percentage is 60%, in chapter 8 the percentage is 56%, in chapter 9 the percentage is 54%, and in chapter 10 the percentage is 61%. As for the entire chapter in semester 2, 55% conformity was obtained, this means that the implementation of bloom taxonomy in the textbook is in the category of less.